Carbonic anhydrase I–II autoantibodies and oxidative status in long-term follow-up of patients with Crimean–Congo haemorrhagic fever. (1st January 2018) - Yilmaz, Hülya; Kostakoğlu, Uğur; Demir, Selim; Aksoy, Firdevs; Menteşe, Ahmet; Karahan, Süleyman Caner; Köksal, İftihar and Alver, Ahmet and Yilmaz, Gürdal
Abstract: Context: Crimean–Congo haemorrhagic fever (CCHF) is a life-threatening acute febrile haemorrhagic disease. Objective: This study was to measure levels of the oxidative stress biomarkers malondialdehyde (MDA), total oxidant status (TOS), total antioxidant status (TAS) and oxidative stress index (OSI) and of CA I–II autoantibodies as biomarkers for autoimmunity and course of disease in patients with CCHF. Methods: Seventy CCHF patients and 39 healthy control volunteers were included in the study. Results: Serum MDA and TAS levels were significantly higher ( p < .0001) and serum TOS and OSI levels were significantly lower ( p < .0001) in both the acute period and at 6th-month follow-up in the CCHF patients compared to the healthy volunteers. CA II levels were significantly higher in the acute period compared to the healthy volunteers ( p < .005) and were significantly lower at 6th-month follow-up ( p < .05). Conclusion: Serum MDA and CA II autoantibodies appear to reflect oxidative stress status and disease progression in CCHF and may be used as biomarkers for oxidative stress and disease progression.